Kunraja Media Development (Aksara Jawa Uno Card) On Javanese Script writing Materials In Elementary Schools - Nur Rofiqoh; Nanang Khoirul Umam; Iqnatia Alfiansyah (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
This study aims to develop KUNRAJA media on Javanese script writing material in elementary schools in grade III UPT SD Negeri 43 Gresik for the 2020/2021 school year. The process of developing learning media uses the modified and simplified ADDIE model, namely, analysis (Analysis), design (Design), development (Development), implementation (Implementation) and evaluation (Evaluation). The results of the development of learning media in the form of KUNRAJA media contain material for writing Javanese script. Sources of data in this development research are material experts and media experts totaling 4 validators and class III students with a total of 28. The data collection used is the validation of learning media and student learning outcomes tests. With data analysis, namely, analysis of the validity of learning media, analysis of the practicality of learning media and the effectiveness of learning media. Based on the results of the descriptive analysis of the validation data, it was obtained that the development of the KUNRAJA media on the Javanese script writing material in elementary schools met the good criteria, as follows: a) The results of the validation of learning media conducted by 4 validators obtained a percentage of 100% by material experts 1 and a percentage of 100% by material expert 2 with a total average rating of 100%, and a percentage of 100% by media expert 1 and a percentage of 92.5% by media expert 2 with a total average rating of 96.25% which is categorized as valid and can be used in the learning process, b) Categorized as practical from the results of the analysis in the practicality of learning media by the validators indicating that the media can be used with little or no revision. c) while in the learning outcomes test, students who scored 70 were 28 students with a percentage of 93.1% which was categorized as effective for use in the learning process. Keywords: ADDIE Model, KUNRAJA, Javanese Script.